Investigation of Mechanical Properties of Polypropylene Film as Vacuum Packaging Material for Dried Fish - Mohammed, I. A.; Adedipe, O.; Jiya, Y. A.; Ayuba, A. B.; Obanimomo, K. T.; Bala, K. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
This study investigated the mechanical properties of three sets of polypropylene packaging films and existing dried fish packaging films and the quality of dried fish packaging in Nigeria... The polypropylene packaging films were produced in three batches A, B and C with thicknesses of 130µm, 150µm and 180µm respectively. The results showed that samples A, B and C had tensile strengths of 48N/mm2, 51.8N/mm2 and 61N/mm2 with Elongation at Break of 690.2%, 729.8% and 760% respectively. Also, the Dart Impact Strength of the samples were observed to be 191g/130µm, 208g/150µm and 231g/180µm respectively. Additionally, samples N and K (existing fish packaging films) had tensile strengths of 34.6N/mm2 and 31.2N/mm2 and Elongation at Break of 279.2% and 267.2% respectively. Furthermore, it was revealed that sample N exhibited better mechanical properties than sample K, while the produced polypropylene packaging films had the best mechanical properties among the samples tested. Using modern systems such as vacuum packaging and modified atmosphere packaging (MAP) techniques, fish packaging and storage was improved. This research is important in light of the significant increase in aquaculture activities in Nigeria due to increased fish production and government intervention in developing the sector, since it offers good moisture barrier properties, transparency and sealability with good cost efficiency and recyclability.It helps to preserve and protect the product’s quality, flavor and shelf life while providing a visually appealing package for consumers.